Definisi dan Peta Konsep Ilmu Pendidikan Islam Perspektif Hasan Langgulung - Aliya Zulva Ahsani; Aulia Shifa Alshafiera; Anggraini Citra Fatmala; Mohammad Faizin (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
This study aims to analyze the definition and concept map of Islamic Education (IPI) within the philosophical framework of Prof. Dr. Hasan Langgulung. IPI is strategically positioned as a discipline that bridges theoretical studies and educational practices in responding to contemporary challenges, while also serving as a foundation for character formation. The method used is library research with a qualitative approach, analyzing primary and secondary documents to synthesize a complete IPI concept map. The results of the study show that Langgulung defines IPI comprehensively as a normative field of science, exploring the process of multi-dimensional human growth (physical, soul, mind, spirit), and utilizing integrative sources of knowledge (revelation, reason, experience). This approach is based on three solid philosophical pillars: Ontology (human nature and fitrah), Epistemology (integration of revelation, reason, and experience), and Axiology (utility values to form a perfect human being). Langgulung's thinking elevates the discussion of IPI from the operational level (Tarbiyah, Ta'lim, Ta'dib) to the philosophical level, providing a solid foundation for IPI as a complete discipline.The ultimate goal is to produce a perfect human being capable of fulfilling the balanced roles of 'Abdullah (servant of God) and Khalifatullah fil Ardh (leader on earth), by optimizing the full potential of human nature. This educational model is considered relevant in contemporary discourse to integrate religious and general knowledge and address the moral crisis.